Literature Review Using Think Talk Write (TTW) Cooperative Learning Model in Students' Mathematical Reasoning Ability - Evi Widianingrum; Dewi Netta Febrianti; Savitri Wanabuliandari (Mathematics Education Journal, 2022)
The purpose of this research is to analyze Think Talk Write (TTW) learning whether this model is effective in improving students' mathematical reasoning abilities. This type of research is a literature review related to the theory of the Think Talk Write (TTW) type cooperative learning model and mathematical reasoning abilities. This research uses library materials as the main data source that discusses the effectiveness of using cooperative learning models to improve students' mathematical reasoning abilities. The selection of sources from the literature review is chosen according to the development of the journal for the last 5 years, namely 2018 to 2022. Reasoning ability is the ability to draw conclusions or make new statements based on previous statements. For cooperative learning model type Think Talk Write (TTW) is an activity to think about reading material by listening, criticizing, and providing solutions. The results of this study indicate that increasing mathematical reasoning ability is more effective using Think Talk Write (TTW) compared to conventional learning, because the use of Think Talk Write (TTW) type learning model will make students understand the material better because they learn from thinking, compiling, testing. , reflect, and write down ideas.